ENHANCEMENT IN SUPERCONDUCTING PROPERTIES OF Y-BA-CU-O THIN-FILMS BY POSTANNEALING IN AN INERT ATMOSPHERE - KIM, YH; HAHN, TS; CHOI, SS; PARK, SJ (CHAPMAN HALL LTD, 1992)
Y-Ba-Cu-0 superconducting thin films were produced by ex situ r.f. magnetron sputtering. In the post-annealing procedure, several annealing conditions which were scheduled for heating rate and annealing atmosphere were tried systematically to determine major factors affecting the characteristics of post-annealed superconducting thin films. From the results of the study, it was found that the characteristics of the films are strongly dependent on the heating atmosphere rather than the heating cycle or heating time. Films with a high transition temperature were obtained by treatment in an argon atmosphere; this is considered to be attributable to the rapid atomic diffusion in tetragonal YBa2Cu3O7-x due to the high oxygen vacancy concentration and the expanded lattice in an inert atmosphere during heat treatment.
Keywords: EVAPORATION; SILICON; INSITU